Efficacy of Glucomannan-Containing Yeast and Glucomannan Extracted from Amorphophallus oncophyllus Against Aflatoxins in Broiler Chicken - Susanto , Agus; Laconi, Erika B.; Astuti, Dewi Apri; Bahri, Syamsul (International Journal of Poultry Science, 2015)
The objective of the study was to evaluate and compare the efficiency of glucomannan extracted from Amorphophallus oncophyllus (GRE) with commercial aflatoxin binder glucomannan yeast product (GYP) in broiler chicken fed aflatoxin contaminated feed. A total of 63 one day old chicks were assigned to 9 equal groups according to dietary treatments: A (basal feed), B (basal feed+aflatoxin 50 μg/kg), C (basal feed+aflatoxin 2 mg/kg), D (basal feed+aflatoxin 50 μg/kg+GYP 1 g/kg), E (basal feed+aflatoxin 50 μg/kg+GRE 1 g/kg), F (basal feed+aflatoxin 50 μg/kg+GRE 2 g/kg), G (basal feed+aflatoxin 2 mg/kg+GYP 1 g/kg), H (basal feed+aflatoxin 2 mg/kg+GRE 1 g/kg) and I (basal feed+aflatoxin 2 mg/kg+GRE 2 g/kg). The body weight decreased significantly (p